Polityka monetarna Polski w związku z wejściem Polski do strefy euro - Noga, Marian (Polish Monetary Policy in Relation to Poland's Joining the Euro Zone, 2006)
In his paper the author presents benefits from Polish accession to the euro zone. He analyses conditions of this process and shows two possible scenarios how Poland should realise the conception of entering the euro zone. In the paper it is shown how Polish active monetary policy could help joining the euro zone.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 56-62